2023
DOI: 10.1021/acs.macromol.2c02486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of POSS Size on the Porosity and Adsorption Performance of Hybrid Porous Polymers

Abstract: Polyhedral oligomeric silsesquioxanes (POSS), with unique cage-like three-dimensional (3D) structures, have been considered as promising nanoblocks for novel hybrid porous polymers (HPPs). To date, T 8 POSS-based HPPs have been extensively studied, while the potential of larger POSS remains elusive and intriguing. Herein, we report the synthesis of a series of T 8 , T 10 , and T 12 POSS-based HPPs (T 8 TPM, T 10 TPM, and T 12 TPM) and investigate their size-dictated structure−property relationships. These nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…[5,45] As for PT 10 N 10 and PT 12 N 12 , it is obviously that they possess lower k values than PT 8 N 8 even at same T n N n loadings (Figure 3c), it may be due to the incorporation of larger cavity from larger POSS. [15,28,32,40] Among them, PT 12 N 12 -40 has the minimum k value (2.10 at 10 3 Hz). Compared with the decrease rates of the k values (compared to the k value of PT 8 N 8 -x) for PT n N n materials, we deduce that the contribution of larger POSS to the k values is considerable even only 5 wt% T n N n contained (consists of ≈0.9 wt% POSS cage).…”
Section: Preparation Structures and Morphologies Of Pt 8 N 8 Pt 10 N...mentioning
confidence: 99%
See 1 more Smart Citation
“…[5,45] As for PT 10 N 10 and PT 12 N 12 , it is obviously that they possess lower k values than PT 8 N 8 even at same T n N n loadings (Figure 3c), it may be due to the incorporation of larger cavity from larger POSS. [15,28,32,40] Among them, PT 12 N 12 -40 has the minimum k value (2.10 at 10 3 Hz). Compared with the decrease rates of the k values (compared to the k value of PT 8 N 8 -x) for PT n N n materials, we deduce that the contribution of larger POSS to the k values is considerable even only 5 wt% T n N n contained (consists of ≈0.9 wt% POSS cage).…”
Section: Preparation Structures and Morphologies Of Pt 8 N 8 Pt 10 N...mentioning
confidence: 99%
“…have been considered as ideal pore generators for reducing the materials' k values. [15,[25][26][27][28][29][30][31][32] Meanwhile, the organic-inorganic hybrid nature and high reactivity of POSSs endow the resulting materials high thermal [28,[32][33][34][35] and mechanical performance, [36,37] large surface area and pore volume, [38][39][40][41] and unique surface properties. [42,43] Recently, we demonstrated that larger POSS (i.e., T 10 and T 12 POSSs) is better nano-building block and filler for fabricating thermally and mechanically robust low-k materials.…”
Section: Introductionmentioning
confidence: 99%
“…45 In addition, Fu et al have reported the different functional POSS such as (T 8 , T 10 , and T 12 ) units with the triptycene components to form organic/inorganic hybrid POPs. 46 Energy density, power capacity, and long cycle stability are essential requirements for an electrode material in energy storage devices. Considering these three factors, we inserted a highly functional unit into a network structure to be a new material and made it a component of an energy storage device.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Benefiting from the extensive functional sites, Fang et al synthesized a 3D stp-topologized COFs with a porphyrin or metalloporphyrin building unit . In addition, Fu et al have reported the different functional POSS such as ( T 8 , T 10 , and T 12 ) units with the triptycene components to form organic/inorganic hybrid POPs …”
Section: Introductionmentioning
confidence: 99%
“…However, the undesired consequence is the production of waste, which has to be further processed. The new strategies for water remediation are based on carbon, polymeric and organic materials, inorganic composites, and hybrid inorganic–organic materials. The aforementioned materials are employed as adsorbents, photocatalysts, and biocatalysts in water recovery processes. Although numerous methods are available for water remediation, adsorption has been recognized as a method of choice, due to its efficiency, simple design, and performance.…”
Section: Introductionmentioning
confidence: 99%